"Christmas Balls": A Christmas Carol by the Adolescent Cancer Patients of the Milan Youth Project. Issue 2 (March 2017) - Ferrari, Andrea; Signoroni, Stefano; Silva, Matteo; Gaggiotti, Paola; Veneroni, Laura; Magni, Chiara; Casanova, Michela; Chiaravalli, Stefano; Capelletti, Mirko; Lapidari, Pietro; Clerici, Carlo Alfredo; Massimino, Maura
The Youth Project is a program developed at the Pediatric Oncology Unit at the Istituto Nazionale Tumori in Milan, dedicated to adolescents and young adults with cancer. Among its various goals, the Youth Project organizes structured creative activities with the support of professionals, with the objective of offering young people a new way to express their hopes and fears. This article describes a project centered around music: patients created a Christmas carol with the help of musicians and authors. The adolescents explained with their own words the meaning of the lyrics, telling the story of a Christmas spent in a cancer hospital ward.